2018
DOI: 10.1111/jgh.14270
|View full text |Cite
|
Sign up to set email alerts
|

Burden of non‐alcoholic fatty liver disease in Australia

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the commonest cause of chronic liver disease in the Australian population, although precise estimates of prevalence are lacking. NAFLD may progress to liver fibrosis, cirrhosis, decompensated liver disease, and liver cancer and is becoming an increasingly common indication for liver transplantation in Australia and New Zealand. There is an extrahepatic burden of NAFLD extending beyond the liver, which is manifested by an increased risk of developing cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 110 publications
(204 reference statements)
1
44
0
Order By: Relevance
“…The prevalence of NAFLD is increasing rapidly in the Western world, mainly due to obesity and type 2 diabetes, becoming the most prevalent chronic liver disease in the Australian population . Its pathophysiology includes overnutrition, sedentary life, genetic factors and insulin resistance .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD is increasing rapidly in the Western world, mainly due to obesity and type 2 diabetes, becoming the most prevalent chronic liver disease in the Australian population . Its pathophysiology includes overnutrition, sedentary life, genetic factors and insulin resistance .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of NAFLD patients are asymptomatic, and a recent international, multicenter, retrospective cohort study of NAFLD patients has demonstrated that the fibrotic stage is independently associated with the overall and liver‐related mortality . Among NAFLD patients, the prevalence of Nonalcoholic steatohepatitis (NASH) and fibrosis stages 3–4 is significant, being found in 15–26% and 3–10% of patients, respectively …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Among NAFLD patients, the prevalence of Nonalcoholic steatohepatitis (NASH) and fibrosis stages 3-4 is significant, being found in 15-26% and 3-10% of patients, respectively. 9 Controlled attenuation parameter (CAP) and transient elastography (TE) are noninvasive and time-saving diagnostic tools that are used to determine liver steatosis and fibrosis concurrently. A recent study of repeating liver stiffness measurement (LSM) using TE in NAFLD patients showed high sensitivity on TE, with a cut-off value < 7.9 kPa demonstrating a 100% negative predictive value for septal or bridging fibrosis and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Australia is well placed to conduct collaborative studies such as those needed to test promising biomarker and physical investigations that characterise those patients in need of major interventions. In the meantime, we strongly agree that greater public and professional awareness of fatty liver as a common accompaniment of overweight and metabolic obesity is needed . Given the strong links between NAFLD and risk of type 2 diabetes, cardiovascular disease and common cancers, even those cases in which the liver disease is minor can benefit enormously from lifestyle intervention, irrespective of whether referral to a liver clinic is activated or not.…”
mentioning
confidence: 96%
“…While their finding that obesity and glucose intolerance are the usual risk factors for significant liver disease with NAFLD is well supported by the literature, we were surprised that NAFLD formed only 7% of referrals to those clinics. Given that community prevalence of NAFLD in most global communities is at least 30% and estimates for Australia are similar, this low frequency of referrals to Melbourne liver clinics deserves comment.…”
mentioning
confidence: 99%